Um processo para o uso de linguagens de consulta em código fonte - Cantarelli, Gustavo Stangherlin (2012)
The search in the source code is gaining more and more space because of the increasing complexity of current software systems and also the need for improvements in source code. Although the paradigms of object-oriented programming and aspect-oriented programming have several features to improve code reuse and clarity when maintenance of code is required, developers tend to reduce productivity because of problems on locating the parts to be corrected or improved. Aiming maintenance activities, this paper presents a search code process that can be applied to source code repositories. This process is exemplified through three instantiations: searches in object-oriented code using SPARQL and SQL, and aspect-oriented code using XML, suggesting that its use may be of great value for any combination of tools and query languages.